The Gulf Information War| The Gulf Crisis and Narratives of Emotionality in Nepal's English-Language Press - Subin, Paul (USC Annenberg, 2019)
This study examines the media discourse on the Gulf diplomatic crisis and its effect on one of the most marginalized populations in Qatar: Nepali migrant workers. Although the diplomatic crisis made news headlines across the Middle East, Nepal-based newspapers were the only ones to cover the vulnerable migrant worker population in some detail. In writing about this population, three prominent English-language publications in Nepal, The Kathmandu Post, Republica, and People’s Review, employed emotional storytelling. Drawing on Wahl-Jorgensen’s notion of the “strategic ritual of emotionality,” this study specifically analyzes the use of emotion in the three publications’ news coverage. The study finds that the publications engaged in the ritual of emotionality not by assigning that function to external news sources, as is common in Western newspapers, but mainly through their own journalists and opinion writers who narrated their subjective viewpoints and concerns. This unreserved embrace of emotions and subjectivity in newswriting illuminates a unique, cultural mode of producing journalism.
Keywords: Media and emotion; Strategic ritual of emotionality; Gulf crisis; Qatar; Nepali media; Nepali migrants; Nepal; 63 Sociología::6306 Sociología del trabajo::6306.07 Sociología de los medios de comunicación de masas; ODS 10 - Reducción de las desigualdades; ODS 8 - Trabajo decente y crecimiento económico; ODS 16 - Paz, justicia e instituciones sólidas; ODS 17 - Alianzas para lograr los objetivos